The Influence of Parents' Social Status and Economic Conditions on Social Studies Learning Achievement of Elementary School Students 25 Madello Soppeng regency - A Hardiyanti; Shermina Oruh; Andi Agustang (JED (Jurnal Etika Demokrasi), 2022)
The economic role of parents, in general, can be said to have a positive relationship to increasing student learning achievement because students' teaching and learning process requires tools or a set of teaching or learning. The aims of this study are 1) to find out whether social status affects the social studies learning achievement of students at SD 25 Madello, Kabupaten Soppeng., 2) To find out whether the economic conditions of parents affect the social studies learning achievement of students at SD 25 Madello, Soppeng Regency., 3) To find out whether the social status and economic conditions of parents affect the social studies learning achievement of students at SD 25 Madello, Soppeng Regency. This research method uses quantitative expost facto research through a correlational approach. The sampling technique of this study is a probability technique with 43 students from grades III, IV, V. The results of this study and alternative hypothesis testing (H3) there is a significant influence between social status and parents' economic condition on social studies learning achievements of elementary school students. 25 Madello, Soppeng Regency.Peranan ekonomi orang tua secara umum dapat dikatakan mempunyai hubungan yang positif terhadap peningkatan prestasi belajar peserta didik ini, disebabkan proses belajar mengajar peserta didik membutuhkan alat-alat atau seperangkat pengajaran atau pembelajaran. Tujuan dari penelitian ini yakni: 1) untuk menganalisis apakah status sosial berpengaruh terhadap prestasi belajar IPS peserta didik SD 25 Madello Kabupaten Soppeng., 2) Untuk mengetahui apakah kondisi ekonomi orang tua berpengaruh terhadap prestasi belajar IPS peserta didik SD 25 Madello Kabupaten Soppeng., 3) Untuk menganalisis apakah status sosial dan kondisi ekonomi orang tua berpengaruh terhadap prestasi belajar IPS peserta didik SD 25 Madello Kabupaten Soppeng. Metode penelitian ini menggunakan kuantitatif dengan jenis penelitian expost facto melalui pendekatan korelasional. Teknik sampling penelitian ini adalah teknik probality dengan  subjek penelitian sejumlah  43 siswa dari kelas III, IV, V. Hasil dari penelitian ini dan pengujian hipotesis alternatif (H3) ada pengaruh yang signifikan antara status sosial dan kondisi ekonomi orangtua terhadap prestasi belajar IPS peserta didik SD 25 Madello Kabupaten Soppeng.